Metodologi Al-Durar al-Wafirat bi Halli Alfaz al-Raudhat fi Qiraati al-Imam Hamzah al-Zayyati karya Syeikh Nuh Jamaluddin al-Kelantani - Nik Muhammad Fadlan Nik Mahmood; Khairul Anuar Mohamad; Anuar Hasin; Mohd Zaini Zakaria; Muhammad Hana Fizi Abdullah (Academic Inspired Network, 2026)
Tier 3